Analysis of Digital Television Signal System Based on Gain and Information in Malang City Area - Zakaria, Muhammad Nanak; Hadiwiyatno, Hadiwiyatno; Anugerah, Marcelino Dwantara (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The transition to digital terrestrial television (DTT) broadcasting necessitates rigorous signal quality assessment to ensure reliable service. This study presents a field measurement and analysis of DTT signal characteristics in the Malang City area, focusing on critical parameters such as gain, signal-to-noise ratio (SNR), and bit error rate (BER). Measurements were conducted using a Signal Hound USB-SA44B spectrum analyzer coupled with a calibrated measurement antenna. The Spike software platform facilitated real-time spectrum analysis and data capture across allocated DTT channels. Results indicate significant variation in signal integrity across different locations. The average measured signal gain was -65 dBm, with SNR values ranging from 18 dB to 25 dB depending on topography and obstructions. A strong correlation was observed between suboptimal gain values (< -70 dBm) and increased BER, leading to pixelation and service dropouts. Furthermore, spectrum analysis revealed the presence of adjacent channel interference in congested urban zones. The study concludes that while core urban areas in Malang generally meet minimum reception thresholds, fringe and obstructed areas suffer from degraded signal quality. These findings underscore the importance of strategic transmitter placement and the potential need for signal repeaters to achieve comprehensive coverage, providing actionable insights for network planners and broadcast engineers